Assessment of endoscope reprocessing at World Gastroenterology Organisation training centers using adenosine triphosphate testing - Visrodia, Kavel; Jones, Dianne; Jennings, Melissa; Conway, Catherine; Burgos, Herbert; Malani, Jioji; Ogutu, Elly; Pausawasdi, Nonthalee; Sabbagh, Luis; Leddin, Desmond; Kassmeyer, Blake; Lennon, Ryan J.; Topazian, Mark D. (Endoscopy International Open, 2024)
Background and study aims Adequacy of endoscope disinfection in resource-limited settings is unknown. Adenosine triphosphate (ATP) testing is useful for evaluation of endoscope reprocessing, and ATP <200 relative light units (RLUs) after manual endoscope cleaning has been associated with adequacy of endoscope disinfection.Methods Consecutive endoscopes undergoing reprocessing at five World Gastroenterology Organisation (WGO) training centers underwent ATP testing before and after an on-site educational intervention designed to optimize reprocessing practices.Results A total of 343 reprocessing cycles of 65 endoscopes were studied. Mean endoscope age was 5.3 years (range 1–13 years). Educational interventions, based on direct observation of endoscope reprocessing practices at each site, included refinements in pre-cleaning, manual cleaning, high-level disinfection, and endoscope drying and storage. The percentage of reprocessing cycles with post-manual cleaning ATP ≧200 decreased from 21.4% prior to educational intervention to 14.8% post-intervention (P=0.11). In multivariable logistic modelling, gastroscopes were significantly less likely (odds ratio [OR] 0.04, 95% confidence interval [CI] 0.01–0.19; P<0.001) than colonoscopes to achieve post-manual cleaning ATP < 200. No other factor (educational intervention, study site, endoscope age) was significantly associated with improved outcomes. Endoscope ID was not significantly associated with ATP values, and sites that performed manual versus automated HLD did not have significantly different likelihood of post-manual cleaning ATP <200 (OR 1.18, 95% CI 0.56–2.50; P=0.67).Conclusions In resource-limited settings, approximately 20% of endoscope reprocessing cycles may result in inadequate disinfection. This was not significantly improved by a comprehensive educational intervention. Alternative approaches to endoscope reprocessing are needed.
Keywords: Quality management; Hygiene; Quality and logistical aspects